Comparative Study of Municipal Waste Management of Two Municipalities in Kushtia District: A Case Study. - Amin, Dr. Md. Ruhul; Mohammad Selim (Brawijaya Journal of Social Science, 2025)
The efficient management of municipal waste is a critical challenge for developing nations, where rapid urbanization and population growth exacerbate the problem. This study provides a comprehensive analysis of municipal waste management practices in Bangladesh, focusing on a comparative study of two municipalities in the Kushtia District: Kushtia Municipality and Kumarkhali Municipality. The research aims to evaluate the effectiveness, sustainability, and environmental impact of current waste management systems in these municipalities. Data were collected through field surveys, interviews with municipal officials, and analysis of secondary sources. The study reveals significant disparities in waste management practices between the two municipalities, attributed to differences in resource allocation, community participation, and policy implementation. Kushtia Municipality, with better financial and infrastructural support, demonstrates more effective waste collection, segregation, and disposal practices compared to Kumarkhali Municipality, which struggles with inadequate resources and lack of public awareness. The findings highlight the need for a more integrated and inclusive approach to waste management, emphasizing community engagement, capacity building, and policy reforms. Recommendations include the adoption of advanced waste processing technologies, enhancement of waste segregation at the source, and the implementation of robust monitoring and evaluation frameworks. This study contributes to the growing body of knowledge on municipal waste management in developing countries and provides actionable insights for policymakers, practitioners, and researchers aiming to improve environmental sustainability and public health in urban areas of Bangladesh.